Aberrant limbic brain structures in young individuals at risk for mental illness. Issue 5 (27th February 2020) - Nogovitsyn, Nikita; Souza, Roberto; Muller, Meghan; Srajer, Amelia; Metzak, Paul D.; Hassel, Stefanie; Ismail, Zahinoor; Protzner, Andrea; Bray, Signe L.; Lebel, Catherine; MacIntosh, Bradley J.; Goldstein, Benjamin I.; et al.
Abstract : Aim: Alterations in limbic structures may be present before the onset of serious mental illness, but whether subfield‐specific limbic brain changes parallel stages in clinical risk is unknown. To address this gap, we compared the hippocampus, amygdala, and thalamus subfield‐specific volumes in adolescents at various stages of risk for mental illness. Methods: MRI scans were obtained from 182 participants (aged 12–25 years) from the Canadian Psychiatric Risk and Outcome study. The sample comprised of four groups: asymptomatic youth at risk due to family history of mental illness (Stage 0, n = 32); youth with early symptoms of distress (Stage 1a, n = 41); youth with subthreshold psychotic symptoms (Stage 1b, n = 72); and healthy comparison participants with no family history of serious mental illness ( n = 37). Analyses included between‐group comparisons of brain measurements and correlational analyses that aimed to identify significant associations between neuroimaging and clinical measurements. A machine‐learning technique examined the discriminative properties of the clinical staging model. Results: Subfield‐specific limbic volume deficits were detected at every stage of risk for mental illness. A machine‐learning classifier identified volume deficits within the body of the hippocampus, left amygdala nuclei, and medial‐lateral nuclei of the thalamus that were most informative in differentiating between risk stages. Conclusion: Aberrant subfield‐specific changes within the limbic system may serve as biological evidence to support transdiagnostic clinical staging in mental illness. Differential patterns of volume deficits characterize those at risk for mental illness and may be indicative of a risk‐stage progression.